Two-year apprenticeships for young people with learning difficulties: a cost-benefit analysis for training firms - Fuhrer, Marc [Verfasser]; Schweri, Jürg [Verfasser] (My University, 2010)
"Education policymakers are currently faced with the challenge of enabling young people with learning difficulties to achieve an upper-secondary level qualification. Switzerland has introduced a new type of combined school/work-based VET programme that lasts two years. One of the key pre-requisites for success of two-year VET programmes is the willingness of host companies to create an adequate number of apprenticeship positions. We therefore examine the costs and benefits of two-year VET programmes for a sample of 409 host companies. Our main findings indicate that, on average, the value of the productive output of apprentices in two-year VET programmes slightly exceeds the overall costs of the training provided by host companies. Firms that operate in a competitive market are thus able to provide apprenticeship training to less capable young people." (Autorenreferat, BIBB-Doku)
Keywords: S 1.3 Berufliche Erstausbildung; P 1.7 Benachteiligte; S 4.3.3 Effizienz & Effektivität des Berufsbildungswesens; Betriebliche Berufsausbildung; Zweijähriger Ausbildungsberuf; Bildungsertrag; Kosten-Nutzen-Relation; Empirische Untersuchung; Quantitative Angaben; Schweiz